Vanessa Place: The Death of the Poetry Book - Hélène Aji (Sillages Critiques)
Many of Vanessa Place’s books proceed from flirting with an end wish: they seem fascinated with the moment of interruption in cycles or processes construed as infinite, like ending an endless sentence (Dies: A Sentence), or navigating the megapolis’s labyrinth (La Medusa). While one can see her work as the manifestation of a retreat from creativity in keeping with her claim that she does not write, but rather, works as a medium to circulate text, one can also approach it as an extreme type of experimentation with expectations, conventions, and the general codes of social order. It is this article’s contention that Vanessa Place systematically appropriates the modes of communication of the digital age to undermine the ideologies at work beneath the surface of all kinds of texts and text formats, through the production of books that re-form and recontextualize these texts to convey their ethical shortcomings.